Rice NIN-LIKE PROTEIN 1 rapidly responds to nitrogen deficiency and improves yield and nitrogen use efficiency - Alfatih, Alamin; Wu, Jie; Zhang, Zi-Sheng; Xia, Jin-Qiu; Jan, Sami Ullah; Yu, Lin-Hui; Xiang, Cheng-Bin (Journal of experimental botany, 2020)
Abstract Nitrogen (N) is indispensable for crop growth and yield, but excessive agricultural application of nitrogenous fertilizers has generated severe environmental problems. A desirable and economical solution to cope with these issues is to improve crop nitrogen use efficiency (NUE). Plant NUE has been a focal point of intensive research worldwide, yet much still has to be learned about its genetic determinants and regulation. Here, we show that rice (Oryza sativa L.) NIN-LIKE PROTEIN 1 (OsNLP1) plays a fundamental role in N utilization. OsNLP1 protein localizes in the nucleus and its transcript level is rapidly induced by N starvation. Overexpression of OsNLP1 improves plant growth, grain yield, and NUE under different N conditions, while knockout of OsNLP1 impairs grain yield and NUE under N-limiting conditions. OsNLP1 regulates nitrate and ammonium utilization by cooperatively orchestrating multiple N uptake and assimilation genes. Chromatin immunoprecipitation and yeast one-hybrid assays showed that OsNLP1 can directly bind to the promoter of these genes to activate their expression. Therefore, our results demonstrate that OsNLP1 is a key regulator of N utilization and represents a potential target for improving NUE and yield in rice. OsNLP1 rapidly responds to N availability, enhances N uptake and assimilation, providing great potential for breeding rice cultivars with high yield and NUE under N-limiting conditions